Robot-assisted pedestrian flow control of a controlled pedestrian corridor. (5th December 2018) - Shan, Liang; Chang, Lu; Xu, Siyuan; Jiang, Chao; Guo, Yi
Pedestrian evacuation and modification of traffic facilities were previously studied to increase the traffic efficiency and the safety of pedestrians. In this article, we first design a new robot-assisted pedestrian control scheme. We consider a different scenario that the inflow of all the entrances to the corridor can be controlled by mobile robots. Based on the collected image data of the experimental corridor, we obtain the regulated pedestrian velocity and build the relationship function between the adjustable motion frequency of the robot and the regulated pedestrian velocity. To achieve the optimal traffic flow in the designed scenario, we set up the macroscopic pedestrian model for the modified unidirectional pedestrian corridor with several controlled entrances. The pedestrian inflow of each entrance is controlled by adjusting the motion frequency of the robot moving in a transverse direction. Then the state feedback controller is designed and the stability of the controller is analyzed based on the Lyapunov stability theory. The theoretical analysis guides the movement of robots. Finally, the simulation results demonstrate the efficiency of the controlled pedestrian system. Our study can flexibly manage the pedestrian flow by applying advanced robotics technology on macro level, which can provide ideal global control effect.